KINERJA GURU PENDIDIKAN JASMANI OLAH RAGA DAN KESEHATAN - Afrizal AZN (UNIVERSITAS BENGKULU, 2016)
This research is aimed to describe the situation of how teacher, proffesionalism is, toward the teaching learning processes of sport and health subject at senior high school I of Ketahun. This research used qualitative method, the data were collected by doing grand tour way, observation, interview and documentation study. The data were analyzed and reduced. The results show that sport and health teachers lack in desingining the lesson plan and giving evaluation to the learning proses.Keywords: professionalism, teachers, sport and health